Bibliometric Analysis of Trends Publications in Scopus Databased themed inulin sausages using R Studios - Sirajuddin, Muhammad Mar'ie; Abdullah, Syukri; Setyanto, Barry Nur (Universitas Ahmad Dahlan, 2021)
Inulin is a dietary fiber that can improve the quality of food products, such as texture, product nutrition, or as a disease-preventing functional food. Inulin has begun to be studied in various studies and applied to meat and poultry, but there have not been many studies assessing whether research on the application of inulin to sausage products is still relevant to be carried out and is still good novelist research, one way to assess the novelty of a research theme. Is to use bibliometric analysis. This study examines the publications in the Scopus database from 2001 to 2022 to measure the number of existing publications using the R method. Studied several aspects, namely 1. Annual Scientific Production 2. Most Relevant Author who has researched inulin sausage, 3. Country Production 4. Most Relevant Sources 5. Most Frequent Words 6. Word cloud related to inulin sausage. The results of the bibliometric analysis show that annual scientific publications show that article production growth has increased every year from 2001 to 2022; the highest was in 2019 with 11 articles. The most relevant Author who has written the most publications is Pollonio Mar, with six articles. Brazil is the country that produces the most articles, namely 28 articles, while the most relevant sources are the journal Meat science which produces six articles, and the most frequent words are inulin with 45 occurrences. Conclusions based on the analyzed data, research on inulin in sausages is still limited. And still very worthy of further research.